Peripheral eosinophilia with eosinophilic gastroenteritis associated with semaglutide: a case report and literature review - Oraijah, Abrar A.; Abdullahi, Hanan Mohamed Moalim; Alidrisi, Ghadah Abdulwahab; Alghamdi, Mansour (International Journal of Research in Medical Sciences, 2026)
Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are widely used for the management of type 2 diabetes mellitus and obesity. Although generally well tolerated, gastrointestinal adverse effects are common, and rare immune-mediated complications have increasingly been reported. We describe the case of a 57-year-old woman with type 2 diabetes mellitus, treated with semaglutide, who presented with a four-month history of chronic epigastric pain, anorexia, and unintentional weight loss. Laboratory evaluation revealed marked peripheral eosinophilia, and endoscopic biopsies of the stomach and duodenum demonstrated extensive eosinophilic infiltration of the lamina propria, confirming a diagnosis of eosinophilic gastroenteritis. Secondary causes, including parasitic infection, allergic disease, and hematologic malignancy, were excluded. Given the temporal relationship between semaglutide initiation and symptom onset, the drug was discontinued. Over the following months, the patient’s symptoms resolved and her eosinophil count normalized, with repeat biopsy confirming histological resolution. This case adds to a growing body of literature describing eosinophilic gastrointestinal and systemic reactions associated with GLP-1 RA therapy. Clinicians should maintain a high index of suspicion for drug-induced eosinophilic disorders in patients on GLP-1 RAs who present with persistent or atypical gastrointestinal symptoms, as early recognition and prompt drug discontinuation can prevent long-term morbidity and lead to complete clinical and histological recovery.